2020
DOI: 10.3390/biomedicines8110450
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Small RNA Signatures in Schwann-Cell-Derived Extracellular Vesicles by the p75 Neurotrophin Receptor and Sortilin

Abstract: Schwann cells (SCs) are the main glial cells of the peripheral nervous system (PNS) and are known to be involved in various pathophysiological processes, such as diabetic neuropathy and nerve regeneration, through neurotrophin signaling. Such glial trophic support to axons, as well as neuronal survival/death signaling, has previously been linked to the p75 neurotrophin receptor (p75NTR) and its co-receptor Sortilin. Recently, SC-derived extracellular vesicles (EVs) were shown to be important for axon growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 69 publications
1
16
0
1
Order By: Relevance
“…Wild-type (WT) Sprague Dawley rats were obtained from Janvier laboratories, while Sort1−/− Sprague Dawley rats (KO) were purchased from Horizon Discovery and custom made, respectively, for breeding at the Animal Facility at Aarhus University. Sort1−/− is a 5 basepair deletion in exon 9 resulting in a stop codon, with subsequent complete destruction of the Vps10p-domain folding [30]. No mRNA splice variants or protein fragments were detected by sequencing or western blot analysis.…”
Section: Animalsmentioning
confidence: 99%
“…Wild-type (WT) Sprague Dawley rats were obtained from Janvier laboratories, while Sort1−/− Sprague Dawley rats (KO) were purchased from Horizon Discovery and custom made, respectively, for breeding at the Animal Facility at Aarhus University. Sort1−/− is a 5 basepair deletion in exon 9 resulting in a stop codon, with subsequent complete destruction of the Vps10p-domain folding [30]. No mRNA splice variants or protein fragments were detected by sequencing or western blot analysis.…”
Section: Animalsmentioning
confidence: 99%
“…Выявлено, что ряд микроРНК, секретируемых в составе ВВ при экспериментальном или клиническом диабетах, вовлечены в патогенез диабетической ретинопатии и нейропатии и в перспективе также могут быть полезны в качестве ранних и достоверных маркеров этих осложнений [47][48][49][50]. Кроме того, вышеперечисленные маркеры могут быть использованы для контроля эффективности терапии данных осложнений [51].…”
Section: варианты взаимодействия экзосом с клеткой без интернализацииunclassified
“…Historically, hyperglycemic conditions, and/or ischemic and hypoxic conditions from vascular modifications were accepted as the most probable cause of axonal degeneration in DN. However, clinical trials have found glycemic control is not sufficient to prevent DN from occurring, suggesting that progression of DN is also mediated by other factors (M. C. Perez-Matos, Gonçalves, Yan, et al, 2020).…”
Section: Diabetic Neuropathymentioning
confidence: 99%